ANALISIS TINJAUAN TERHADAP TINDAK PIDANA ABORSI BERDASARKAN UNDANG-UNDANG NO 36 TAHUN 2009 KESEHATAN - Iswandi, Erik; Guntara, Deny; Abas, Muhamad (LPPM STIH Awang Long, 2023)
Abortion is an act that violates the law because it tries to abort a pregnancy or abort it with various problems and reasons. The reasons for someone having an abortion can be in the form of medical reasons that require an abortion, economic reasons that are not sufficient for the family's needs, social reasons and so on. In (Decision Study Number 333/Pid.Sus/2021/PN Bks), a woman has an abortion on the grounds that if she doesn't have an abortion then she will lose her job while she is the backbone of the family because her husband doesn't work. The purpose of this study is to legally analyze the decision Number 333/Pid.Sus/2021/PN Bks. The research method used is normative juridical with library study data collection methods. The results of this study indicate that the act of abortion is a criminal act regulated in the Health Law and the Criminal Code with several exceptions. The judge decides the case by considering the evidence and facts at trial. The judge in deciding this case was in accordance with the regulations so that the judge's indictment was fair and did not harm the defendant.